Utility of Ultrasonographically Guided Fine Needle Aspiration Cytology in the Diagnosis of Hepatic Masses - Saldanha, Dr. Prema; Abdulla, Dr. Thahseena (International Journal of Innovative Research in Medical Science, 2018)
Background: With technological advances in imaging, previously inaccessible lesions can now be safely sampled by Fine Needle Aspiration Cytology (FNAC) under radiological guidance. It is also possible to ensure a more accurate diagnostic yield often providing an unequivocal diagnosis in both neoplastic and nonneoplastic conditions. This study was done to assess the role of Ultrasonographic (USG) guided FNAC in the evaluation of hepatic masses. Methodology: USG-guided FNAC was done in patients with hepatic masses. The smears made were stained by the Papanicolaou stain and the cytological features were studied. Relevant clinical data and laboratory investigations which corroborated the diagnosis were recorded. Results: A total of 90 liver aspirates were included in the study. Out of these there were 29 cases of hepatocellular carcinoma. In all the cases except one, the serum alpha fetoprotein levels were found to be elevated. There were 49 cases of metastatic tumors, in which the primary site was not known in 15 cases. The morphology of these secondary tumors was that of an adenocarcinoma. In the remaining 34 cases the primary tumor was found in various organs including the lung, pancreas, stomach, small intestine, breast, ovary, oral cavity and thyroid. There were six non-neoplastic lesions including regenerative nodules, hydatid cyst, tuberculosis, and abscess. In six cases the material was inadequate for definite diagnosis. Conclusion: USG-guided FNAC is a rapid, inexpensive and relatively safe technique for making a cytological diagnosis. A high degree of accuracy due to precise localization of the needle can be achieved and requires close co-operation between the clinician, the radiologist and the pathologist.